2015
DOI: 10.1123/apaq.2014-0164
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Interventions for Children and Youth With Visual Impairments

Abstract: The authors conducted a systematic literature review on physical activity interventions for children and youth with visual impairment (VI). Five databases were searched to identify studies involving the population of interest and physical activity practices. After evaluating 2,495 records, the authors found 18 original full-text studies published in English they considered eligible. They identified 8 structured exercise-training studies that yielded overall positive effect on physical-fitness and motor-skill o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 31 publications
(76 reference statements)
0
8
0
1
Order By: Relevance
“…Of these, 24 were met the inclusion criteria which were: Diagnosis of vision impairment by a doctor or optometrist according to the children's medical records (no absolute blindness or only light perception), parents' consent, lack of physical, sensory, cognitive or motor impairment, and no participation in other clinical interventions at the same time. Due to the lack of such interventions in these children, we first examined the treatment protocol according a panel of experts [13] included four faculty members of the Department of Occupational Therapy, University of Social Welfare and V Rehabilitation Sciences (expert in perceptual-motor issues), and one optometrist (a low vision specialist).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 24 were met the inclusion criteria which were: Diagnosis of vision impairment by a doctor or optometrist according to the children's medical records (no absolute blindness or only light perception), parents' consent, lack of physical, sensory, cognitive or motor impairment, and no participation in other clinical interventions at the same time. Due to the lack of such interventions in these children, we first examined the treatment protocol according a panel of experts [13] included four faculty members of the Department of Occupational Therapy, University of Social Welfare and V Rehabilitation Sciences (expert in perceptual-motor issues), and one optometrist (a low vision specialist).…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have examined the developmental delays of gross, fine, and perceptualmotor skills of children with visual impairment [7][8][9][10]. However, few studies have been conducted in the field of perceptual-motor intervention of these children and no specific framework for training has been provided [11,13]. Since motor problems are very important in various aspects of development, disability is more pronounced in these aspects [5,6,12].…”
mentioning
confidence: 99%
“…Entretanto aqueles que eram moderadamente ativos na infância podem ter mantido o nível de atividade física ou aumentado de forma discreta, visto que o desfecho nível de atividade física foi dicotomizado em inativo (inativo ou cumpre pouco as recomendações) e ativo (cumpre parcialmente as recomendações e cumpre as recomendações). Entretanto, como afirmam Furtado, Allums-Featherston, Lieberman, & Gutierrez (2015), são poucos os estudos de intervenção em crianças com deficiência visual com relação a atividade física regular, sendo que os poucos conduzidos não possuem um bom delineamento. Ficando desta forma uma lacuna sobre a mudança dos níveis de atividade física na infância e sua relação direta no nível de atividade física no adulto.…”
Section: Discussionunclassified
“…The research questions, search strategy and inclusion/exclusion criteria were determined prior to commencing the search. Although the initial research plan was to review studies across all age categories, the population of interest was restricted to adults (aged 18 years and over) following the initial search as a recent systematic review among children and adolescents was identified 21. We included experimental studies focusing on a physical activity intervention or those examining interventions with a clear physical activity component.…”
Section: Methodsmentioning
confidence: 99%